2012
DOI: 10.1088/0741-3335/54/12/124042
|View full text |Cite
|
Sign up to set email alerts
|

High-energy-density plasmas generation on GEKKO-LFEX laser facility for fast-ignition laser fusion studies and laboratory astrophysics

Abstract: The world's largest peta watt (PW) laser LFEX, which delivers energy up to 2 kJ in a 1.5 ps pulse, has been constructed beside the GEKKO XII laser at the Institute of Laser Engineering, Osaka University. The GEKKO-LFEX laser facility enables the creation of materials having high-energy-density which do not exist naturally on the Earth and have an energy density comparable to that of stars. High-energy-density plasma is a source of safe, secure, environmentally sustainable fusion energy. Direct-drive fast-ignit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…Recent developments (Daido et al 1986;Courtois et al 2005;Fujioka et al 2012Fujioka et al , 2013Albertazzi et al 2014) in the generation of strong magnetic fields on large scales using high-power laser techniques raise the question as to what use might be made of magnetic fields with flux densities that perhaps even reach 1 kT. Theoretical work also continues to indicate that self-generated longitudinal magnetic fields can occur in laser-plasma interactions (Liu et al 2013).…”
Section: Role Of a Static Longitudinal Magnetic Fieldmentioning
confidence: 99%
“…Recent developments (Daido et al 1986;Courtois et al 2005;Fujioka et al 2012Fujioka et al , 2013Albertazzi et al 2014) in the generation of strong magnetic fields on large scales using high-power laser techniques raise the question as to what use might be made of magnetic fields with flux densities that perhaps even reach 1 kT. Theoretical work also continues to indicate that self-generated longitudinal magnetic fields can occur in laser-plasma interactions (Liu et al 2013).…”
Section: Role Of a Static Longitudinal Magnetic Fieldmentioning
confidence: 99%
“…laser-driven coils (Daido et al 1986, Fujioka et al 2012, Fujioka et al 2013. A body of simulation work has been carried out at LLNL on the assembly of such fields, and the characterization of their advantages for electron transport, which we shall review here.…”
Section: Axial Magnetic Field Approachmentioning
confidence: 99%
“…Work is ongoing to elucidate the difference in field dynamics. Magnetic field generation by laser-driven coils (Daido et al 1986) was demonstrated experimentally in the 1980s, and has recently been suggested as a divergence mitigation approach for fast ignition (Fujioka et al 2012). In this scheme, a coil connects two plates, one of which is struck by a kJ-class, long pulse (∼ ns) laser.…”
Section: Axial Magnetic Field Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface muon production [20] from proton beam interaction with a solid target presents a local maximum in the range of 300-350 MeV [19,[21][22][23][24] . Experiments on laserdriven proton acceleration by high power, ps laser pulse interaction with ultrathin solid targets or with specific solid target configuration could be planned and performed in existing kJ/PW laser facilities as the GEKKO-LFEX [25,26] , the ORION [27] and the PETAL [28,29] . Recent development of kJ/PW laser systems [30] in worldwide laser facilities enable to perform preliminary experiments on muon production by proton beam interaction with solid targets and investigate fusion process in magnetized plasmas with applications to astrophysics [28][29][30] or energy production [25,26,[28][29][30] .…”
Section: Introductionmentioning
confidence: 99%